Overview of Interest in Petanque Sports in Lambur II Village, Tanjung Jabung Timur Regency Jambi Province - Sukendro Sukendro; Ramadhani Ramadhani; Boy Indrayana; Rasyono Rasyono; Turino Adi Irawan; Putri Ayu Lestari (UNIB Press, 2022)
This study aims to determine the cause of the lack of interest of the people of Lambur II Village, Tanjung Jabung Timur Regency in the petanque sport. The research used is a descriptive survey by describing the results of public interest in the Petanque sport. The variable used in this study is a single variable. The study began with the activity of distributing questionnaires to the sample, then data analysis was carried out on the results obtained from the research sample. The results showed that the review of interest in the Petanque sport in Lambur II Village, Tanjung Jabung Timur Regency, Jambi Province in the medium category was 57.93%. From the results that have been obtained, it shows that the review of interest in the Petanque sport in Lambur II Village, Tanjung Jabung Timur Regency, Jambi Province has begun to be popular among the public. The conclusion from the research conducted is that the results of the analysis of each factor that affect the interest of the people of Lambur II Village, Tanjung Jabung Timur Regency, Jambi Province and the results of the analysis of each influencing indicator are based on intrinsic factors and each indicator, namely the indicators of interest, attention, and activity is moderate. Then for the interest of the people of Lambur II Village, Tanjung Jabung Timur Regency, Jambi Province towards petanque sports based on extrinsic factors and indicators, namely environmental indicators and indicators of tools and facilities, it can be said that the interest of the people of Lambur II Village, Tanjung Jabung Timur Regency, Jambi Province towards sports petanque is medium.